RISKS ASSOCIATED WITH MEDICAL GLAUCOMA TREATMENT FOR CATARACT PATIENTS: A PROSPECTIVE OBSERVATIONAL COHORT STUDY - Mallikarjun, Ratkal Ashwini; Charlotte, Akshata; Mahendraker, Nalini (Student's Journal of Health Research Africa, 2024)
Background Glaucoma and cataracts are common ocular conditions often found together, posing significant challenges in patient management. The concurrent presence of both conditions can complicate treatment strategies, as glaucoma medications may accelerate cataract formation. This study examines the impact of glaucoma treatment on cataract progression and visual outcomes. Methods This prospective observational cohort study at Mahaveer Institute of Medical Sciences, Telangana, enrolled 80 adults with glaucoma and cataracts. Participants received glaucoma treatment and were monitored for IOP, visual acuity, and cataract progression over six months. Data collected at baseline, 1, 3, and 6 months were analyzed using SPSS. Ethical approval and informed consent were obtained. Results The study included 80 participants with glaucoma and cataracts, with a mean age of 65.4 years. Cataract progression occurred in 35% of participants, with higher rates in those with more severe baseline cataracts. Intraocular pressure (IOP) decreased significantly from 24.1 mmHg at baseline to 16.8 mmHg at 6 months (p < 0.001). Visual acuity worsened considerably over the study period (p = 0.02). Ocular side effects were reported in 31.3% of participants, but these were not significantly correlated with specific glaucoma treatments (p > 0.05). Conclusion The study found that glaucoma medications significantly reduce intraocular pressure but may contribute to cataract progression and a decline in visual acuity. Ocular side effects were common, though not linked considerably to specific treatments. Recommendation We recommend lifelong annual examinations by an ophthalmologist for patients who have had surgery for cataracts. Future studies are needed to assess the long-term glaucoma risk for patients treated with current aspiration techniques.